PENSA study: Study design, recruitment profiles and participant inclusion in multimodal intervention studies: Prevention (nonpharmacological) / Multidomain. (7th December 2020) - Fauria, Karine; Forcano, Laura; Knezevic, Iva; Minguillón, Carolina; Menezes‐Cabral, Sofia; Gispert, Juan Domingo; Sánchez‐Benavides, Gonzalo; Soldevila‐Domenech, Natalia; Boronat, Anna; Cuenca, Aida; Puig‐Pijoan, Albert; Mateus, Julian; et al.
Abstract: Background: A large number of modifiable risk factors for AD have been identified in observational studies, many of which do not appear to exert effects through amyloid or tau. This suggests that primary prevention studies focusing on risk reduction and lifestyle modification may offer benefits. The PENSA Study is a clinical trial aiming at preventing cognitive decline in APOE ‐ ɛ4 carriers with subjective cognitive decline (SCD). The proposed clinical trial design will evaluate the efficacy of epigallocatechin‐3‐gallate (EGCG) in the context of a personalized medicine approach including a multimodal intervention looking at improving person‐centered outcomes in this population. Method: We have established a randomized, double‐blind, multimodal personalized clinical trial with 200 participants (60‐80 years; APOE‐ε4 allele carriers; fulfilling SCD criteria with 2 additional SCD plus supportive features) with 4 arms of 50 participants each (Fig 1). Recruitment is primarily achieved through web‐based forms capturing information about participants' subjective cognitive status. Those participants a priori eligible will be tested for APOE status, and carriers of the APOE‐ε4 allele will be invited to the study. The intervention lasts for 12 months and the multimodal lifestyle approach will include physical activity, dietary, and mental health promotion interventions. Result: The trial's primary efficacy outcome is a modified ADCS‐PACC score. The secondary efficacy outcome will be evaluated by Functional neuronal connectivity (fcMRI) and structural connectivity (MRI). Exploratory outcomes include Microbiota composition, Dietary patterns (metabolomics), additional cognitive performance scores and plasma AD biomarkers assessment. Conclusion: The multimodal intervention approach of PENSA is expected to slow down cognitive decline and improve brain connectivity in a population of APOE‐e4 participants with SCD. The study also intends to evaluate several underlying mechanisms that could explain the efficacy of the intervention in slowing down cognitive decline such changes in brain connectivity, gut microbiota composition, AD biomarkers and biological ageing predictors. Further, this trial will give us information regarding participants' retention and compliance, and therefore feasibility of this kind of high‐demanding engagement prevention studies.